Framing the “Other”: Literary and Media Representations of Pastoral Conflict in Kenya and Uganda - Johnson Ocan; Marus Eton; Joan-Ndamiira Kyarimpa; John Baptist Imokola (Universitas Negeri Semarang, 2026)
Pastoral conflicts in East Africa are frequently narrated through discourses that construct pastoral communities as cultural “others,” shaping public perceptions and policy responses. Although scholarship has examined pastoral conflict from political, environmental, and socio-economic perspectives, less attention has been paid to how literary texts and media narratives together frame pastoral identities across national contexts. This study addresses this gap by comparatively examining representations of pastoral “others” in Kenya and Uganda through literary and journalistic narratives. The study draws on framing theory and the concept of othering to explain how narratives construct social identities by emphasizing difference, marginality, and cultural stereotypes. Methodologically, it adopts a comparative qualitative design that integrates literary analysis with media discourse analysis. The Kenyan case focuses on depictions of the Maasai in the works of Henry Ole Kulet, while the Ugandan case examines media portrayals of Balaalo herders in selected newspaper reports and digital news platforms. Texts were purposively sampled to capture dominant narratives of pastoral conflict and inter-community relations. The findings reveal that both literary and media narratives frame pastoral groups through discourses of cultural alterity, mobility, and contested land relations. However, important differences emerge: Kulet’s fiction tends to humanize the Maasai by foregrounding cultural identity, resilience, and historical marginalization, whereas Ugandan media coverage frequently constructs Balaalo herders through conflict-centered frames that emphasize land disputes, insecurity, and tensions with subsistence farming communities. By juxtaposing literary imagination with media representation, the study demonstrates how narrative forms shape public understandings of pastoral conflict in East Africa.